ANALISIS PERBANDINGAN FRAMEWORK JAVASCRIPT DALAM PENGEMBANGAN APLIKASI WEB MODERN (Kohesi: Jurnal Sains dan Teknologi, 2025)
Website development plays a crucial role in enhancing brand awareness and delivering optimal services in the digital era. Front-end frameworks such as React and Vue have become primary choices for developers due to their ability to accelerate the development process and simplify code management. However, choosing between these two frameworks often leads to confusion due to differences in their approaches, performance, and features. This study aims to analyze and compare React and Vue based on criteria such as performance, flexibility, efficiency, ease of use, and data management using a qualitative method. The results indicate that Vue.js excels in rendering speed, resource efficiency, and ease of use due to its intuitive structure and well-organized documentation. Meanwhile, React.js offers greater flexibility, making it suitable for large-scale projects, and boasts a vast ecosystem, though it requires a steeper learning curve. In terms of data management, Vue provides a structured reactivity system, whereas React relies on additional libraries like Redux. Based on these findings, Vue is recommended for small to medium-sized projects and beginner developers, while React is more suitable for complex projects with experienced teams